2006
DOI: 10.1093/nar/gkl1070
|View full text |Cite
|
Sign up to set email alerts
|

Selenium derivatization of nucleic acids for crystallography

Abstract: The high-resolution structure of the DNA (5′-GTGTACA-C-3′) with the selenium derivatization at the 2′-position of T2 was determined via MAD and SAD phasing. The selenium-derivatized structure (1.28 Å resolution) with the 2′-Se modification in the minor groove is isomorphorous to the native structure (2.0 Å). To directly compare with the conventional bromine derivatization, we incorporated bromine into the 5-postion of T4, determined the bromine-derivatized DNA structure at 1.5 Å resolution, and found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 41 publications
6
78
0
Order By: Relevance
“…Out of these three sequences, only the U267-SeCH 3 DIS variant produced diffraction quality crystals. Interestingly, as reported previously for a 29-SeCH 3 -labeled DNA duplex (Jiang et al 2007), these Sederivatized crystals grew significantly faster and larger than crystals with unmodified RNA, leading to an improvement in the diffraction limit (Table 1). Poorly diffracting crystals and spherulites were obtained with the U266-SeCH 3 DIS RNA, and no crystals were found for the U270-SeCH 3 DIS sequence (Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Out of these three sequences, only the U267-SeCH 3 DIS variant produced diffraction quality crystals. Interestingly, as reported previously for a 29-SeCH 3 -labeled DNA duplex (Jiang et al 2007), these Sederivatized crystals grew significantly faster and larger than crystals with unmodified RNA, leading to an improvement in the diffraction limit (Table 1). Poorly diffracting crystals and spherulites were obtained with the U266-SeCH 3 DIS RNA, and no crystals were found for the U270-SeCH 3 DIS sequence (Fig.…”
Section: Resultssupporting
confidence: 78%
“…29-methylseleno (29-SeCH 3 ) labeling of nucleic acids has been developed as an alternative to two broadly used phasing techniques, to the halogenation of pyrimidines and to soaking crystals in heavy atom salt solutions Teplova et al 2002;Carrasco et al 2004;Jiang et al 2007;Pallan and Egli 2007). The 29-SeCH 3 -labeling method, suited for the determination of RNA structures, relies on the crystallization of RNA molecules that have natural nucleoside(s) substituted for their 29-SeCH 3 -modified counterparts during chemical RNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the chemical and enzymatic incorporation of halogens is primarily limited to the 5-position of pyrimidine nucleosides (such as 5-BrdU as a mimic of T) [33] [34], the lack of multiple choices of derivatization positions has limited the usefulness of the halogen derivatization. Moreover, the possible basestacking disruption, hydration pattern alteration, and backbone perturbation [43] can also limit the applications of the halogen derivatization. In addition, recent reports have indicated that the light sensitivity and instability of halogen derivatives can lead to their decomposition after exposure to UV irradiation, let alone long-time X-ray irradiation during the diffraction data collection [44] [45].…”
mentioning
confidence: 99%
“…We were the first to synthesize Se-derivatized nucleoside phosphoramidites and incorporate them into nucleic acids by solid-phase synthesis. For convenience, recently we have coined the abbreviation SeNA [51], which refers to Se-derivatized nucleic acid. So far, we and other research groups have introduced Se into both DNA and RNA chemically and enzymatically by replacement of selected O with Se at a variety of positions, including O-atoms in the 5'-and 2'-positions, the non-bridging phosphate backbones, and nucleobases [38 -53].…”
mentioning
confidence: 99%
“…The Se-derivatized DNA sequences crystallize under a broader range of buffer conditions [51 -53], and generally have a faster crystal growth rate with higher diffraction quality when compared with the native structure and traditional halogen derivatization. Furthermore, by comparing the Se-derivatization with the conventional Br-derivatization, we found that the Brderivatization caused local perturbations, such as the backbone rotation, the H 2 Onetworking disruption, and the hydrate pattern alteration [51].…”
mentioning
confidence: 99%